Learning English makes it easier to integrate into rapidly changing societies - pcadmin, Kamola Kayumova (Genius Publishing Group, 2025)
This article highlights several ways to learn English effectively and some of the modern learning technologies in language learning as well
Keywords: Language; independent language learning; interactive methods